Disrupted emotional neural circuitry in adolescents with borderline personality traits. (14th May 2019) - Safar, Kristina; Sato, Julie; Ruocco, Anthony C.; Korenblum, Marshall S.; O'Halpin, Helen; Dunkley, Benjamin T.
Graphical abstract: Highlights: It is unknown whether neural circuitry is altered in adolescents with BPD traits. Functional connectivity to emotional faces was examined in this group using MEG. Decreased alpha-band fronto-limbic phase synchrony to angry faces was revealed. Results suggest disrupted interregional neural communication to threatening faces. Abstract: Disruptions in fronto-limbic circuitry have been reported in adults with borderline personality disorder (BPD), yet it is unknown whether dynamic functional neurophysiology is similarly altered in adolescents with high levels of BPD traits. Using magnetoencephalography (MEG) and an implicit perception of emotional faces task, this study investigated task-dependent functional connectivity of eight a priori regions of interest implicated in emotional processing, in 16 females with and without BPD traits. An underconnected network of areas was observed in the BPD-trait group during implicit angry face perception – an effect absent for happy faces. This hyposynchronous fronto-limbic circuit included connections among bilateral amygdalae and bilateral anterior cingulate cortex (ACC), and additional regions implicated in emotion processing. These preliminary, novel results extend existing findings in adults with a diagnosis of BPD, and suggest that disrupted neurophysiological circuitry underlies maladaptive perception of threatening emotional expressions in others, manifests around a key milestone in neurodevelopement, and might contribute to the emotional dysregulation and difficulties with interpersonal relationships commonly found in adolescents high in BPD traits.